ANALISIS PARAMETER AKUIFER BEBAS KOTA PEKANBARU UNTUK KEBERLANJUTAN AIR BAWAH TANAH - Juandi Juandi; Adrianto Ahmad; Edisar Edisar; Syamsulduha Syamsulduha (Program Pascasarjana Universitas Riau, 2013)
Studies have been conducted to analyze the unconfined aquifer parameters City Pekanbaru.Based on the results obtained that the unconfined aquifer transmissivity Pekanbaru City is13,58, value - average yield sfesifik unconfined aquifer by geoelectric measurementpoint in the city of Pekanbaru is 17.67%, average hydraulic conductivity value unconfinedaquifer by geoelectric measurement point in the city of Pekanbaru is 1,87 m / day andunconfined aquifer thickness value based geoelectric measurement point in the city ofPekanbaru is 7,264 m.